Penerapan Model Pembelajaran Think Pair Share Berbantuan Media Wordwall Untuk Meningkatkan Hasil Belajar Kognitif Siswa - Sika Yanti; M. Rahmad; Zuhdi Ma’aruf; Ditha Farliani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study tested the effectiveness of the Think Pair Share cooperative learning model assisted by wordwall media in improving students' cognitive learning outcomes. Using a quasi-experimental method (post-test only nonequivalent control group design), this study involved 73 students of grade X of Pekanbaru Technology High School. The research sample was divided into two groups, namely class X2 as the experimental class and class X1 as the control class. Data were collected through a post-test on the topic of global warming symptoms, then analyzed descriptively and inferentially. The results showed a significant difference. The average score of the experimental class using the model reached 85 (good category), while the control class only obtained an average of 67 (fair category). This proves that the use of the Think Pair Share model assisted by wordwall media is effective in improving students' cognitive learning outcomes.